625 Cluster analysis of weather and pollution features and its role in predicting acute cardiac or cerebrovascular events. (8th December 2021) - Testa, Alberto; Anticoli, Sabrina; Pezzella, Francesca Romana; Mangiardi, Marilena; Di Giosa, Alessandro; Marchegiani, Giada; Gaspardone, Achille; Versaci, Benedetta; Versaci, Francesco; Zoccai, Giuseppe Biondi
Abstract: Aims: The impact of the interplay between weather and pollution features on the risk of acute cardiac and cerebrovascular events has not been entirely appraised. The aim of this study was to perform a comprehensive cluster analysis of weather and pollution features in a large metropolitan area, and their association with acute cardiac and cerebrovascular events. Methods and results: Anonymized data on acute myocardial infarction (AMI) and acute cerebrovascular events were obtained from three tertiary care centre from a single large metropolitan area. Weather and pollution data were obtained averaging measurements from several city measurement stations managed by the competent regional agency for environmental protection, and from the Meteorologic Center of Italian Military Aviation. Unsupervised machine learning was performed with hierarchical clustering to identify specific days with distinct weather and pollution features. Clusters were then compared for rate of acute cardiac and cerebrovascular events with Poisson models. As expected, significant pairwise correlations were found between weather and pollution features. Building upon these correlations, hierarchical clustering, from a total of 1169 days, generated four separate clusters: Cluster 1, including 60 (5.1%) days, Cluster 2 with 419 (35.8%) days, Cluster 3 with 673 (57.6%) days, and Cluster 4 with 17 (1.5%) days, with significant between-cluster differences in weather and pollution features. Notably, Cluster 1 was characterized by low temperatures and high ozone concentrations ( P  < 0.001). Overall cluster-wise comparisons showed significant overall differences in adverse cardiac and cerebrovascular events ( P  < 0.001), as well as in cerebrovascular events ( P  < 0.001) and strokes ( P  = 0.001). Between-cluster comparisons showed that Cluster 1 was associated with an increased risk of any event, cerebrovascular events, and strokes in comparison to Cluster 2, Cluster 3, and Cluster 4 (all P  < 0.05), as well as AMI in comparison to Cluster 3 ( P  = 0.047). In addition, Cluster 2 was associated with a higher risk of strokes in comparison to Cluster 4 ( P  = 0.030). Analysis adjusting for season confirmed the increased risk of any event, cerebrovascular events, and strokes for Cluster 1 and Cluster 2. Conclusions: Unsupervised machine learning can be leveraged to identify specific days with a unique clustering of adverse weather and pollution features which are associated with an increases risk of acute cardiovascular events, especially cerebrovascular events.